2011
DOI: 10.1158/1940-6207.capr-10-0151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emphysema on Lung Cancer Risk in Smokers: A Computed Tomography–Based Assessment

Abstract: The contribution of emphysema to lung cancer risk has been recognized, but the effect size needs to be further defined. In this study, 565 primary lung cancer cases were enrolled though a prospective lung cancer cohort at Mayo Clinic, and 450 controls were smokers participating in a lung cancer screening study in the same institution using spiral computed tomography (CT). Cases and controls were frequency matched on age, gender, race, smoking status, and residential region. CT imaging using standard protocol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 38 publications
4
72
1
Order By: Relevance
“…However, the advantage in our study is that visual assessment does not require additional software and is simple, and previous studies have shown the validity of this approach. [19][20][21][22] In conclusion, emphysema frequently is present on chest CT scans of smokers and predicts early death from COPD or lung cancer. These data provide strong evidence regarding the validity and utility of these studies, one-half of the participants with emphysema (15% of the entire cohort) had normal lung function, and the presence of emphysema was found to predict a diagnosis of lung cancer even among patients with normal spirometry.…”
Section: Resultsmentioning
confidence: 89%
“…However, the advantage in our study is that visual assessment does not require additional software and is simple, and previous studies have shown the validity of this approach. [19][20][21][22] In conclusion, emphysema frequently is present on chest CT scans of smokers and predicts early death from COPD or lung cancer. These data provide strong evidence regarding the validity and utility of these studies, one-half of the participants with emphysema (15% of the entire cohort) had normal lung function, and the presence of emphysema was found to predict a diagnosis of lung cancer even among patients with normal spirometry.…”
Section: Resultsmentioning
confidence: 89%
“…DE TORRES et al [22] showed that emphysema found on computed tomography, but not airflow obstruction, was associated with an increased frequency of lung cancer. Results of lung cancer screening by the Mayo Clinic (Rochester, MN, USA) from multiple logistic regression models showed that emphysema (o5% on computed tomography) was associated with a 3.8-fold increased risk of lung cancer in Caucasians and with higher risks in subgroups that included younger people (,65 yrs of age, OR 4.64), heavy smokers (o40 pack-yrs, OR 4.46), and small-cell lung cancer (OR 5.62) [23]. Emphysema was assessed in these studies by visual semiquantitative scoring of computed tomography images.…”
Section: Epidemiology and Risk Of Lung Cancer In Copd Patientsmentioning
confidence: 99%
“…Impairment of NMC results in the accumulation of respiratory secretions and reduced lung defenses leading to infections, inflammation [4], and perhaps even neoplasia [8]. NMC thus functions as a biomarker of nasal mucosal function [9] and can serve as an early warning system for susceptibility to respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%